Strain Enhanced Visible–Ultraviolet Absorption of Blue Phosphorene/MoX2 (X = S, Se) Heterolayers. Issue 5 (23rd January 2019) - Gu, Di; Tao, Xiaoma; Chen, Hongmei; Ouyang, Yifang; Zhu, Weiling; Peng, Qing; Du, Yong
Abstract : With ultrahigh carrier mobility and large band gap, blue phosphorene (bP) is a promising photoelectronics surpassing black phosphorene and can be further improved by heterostacking. Herein, strain‐engineering of the electronic band gaps and light absorption of two van der Waals heterostructures bP/MoS2 and bP/MoSe2 via first‐principles calculations has been reported. Their electronic band structures are sensitive to in‐plane strains. It is interesting and beneficial that biaxial compressive strain range of −0.02 to −0.055 induces the direct band gap in bP/MoSe2 . There are two critical strains for bP/MoS(Se)2 heterostructures, where the semiconductor–metal transition can be observed. The bP/MoS(Se)2 heterostructures exhibit strong visible–ultraviolet light absorption, which can be further enhanced via biaxial strain. Our results suggest that bP/MoS(Se)2 heterostructures have promising electronics and visible–ultraviolet optoelectronic applications. Abstract : The electronic band structures of van der Waals heterostructures of blue phosphorene (bP)/MoS2 and bP/MoSe2 are sensitive to in‐plane strains. Biaxial compressive strain induces the direct band gap in bP/MoSe2 heterostructures. Both heterostructures exhibit strong visible–ultraviolet light absorption, which can be further enhanced via biaxial strain.